Design Android-Based Student Learning Evaluation Information System at Primagama Bekasi Homeschooling - Corlina Mandana (ENCRYPTION: Journal of Information And Technology, 2024)
Good value data processing will produce learning values ​​as a good evaluation result, in addition, the results of value data processing will be used as one of the benchmarks for student success in completing education at school. Currently, after students have completed daily tests, mid-term tests and final semester tests, the teacher will give students grades by writing them in the liaison book that students bring to each lesson. The purpose of this study is to create an android-based student learning evaluation information system at Homeschooling Primagama Bekasi to facilitate school academics in managing student grades. The research method used is descriptive qualitative with data collection through observation, interviews and documentation. In addition, the author uses a system design tool, namely the Unified Modeling Language (UML) and the Java programming language with a firebase database so that the author can conclude that this information system can make it easier for school administrators to make student learning evaluations at Homeschooling Primagama Bekasi.